Targeted capture and sequencing for detection of mutations causing early onset epileptic encephalopathy. Issue 7 (10th May 2013) - Kodera, Hirofumi; Kato, Mitsuhiro; Nord, Alex S.; Walsh, Tom; Lee, Ming; Yamanaka, Gaku; Tohyama, Jun; Nakamura, Kazuyuki; Nakagawa, Eiji; Ikeda, Tae; Ben‐Zeev, Bruria; Lev, Dorit; et al.
Summary Purpose Early onset epileptic encephalopathies (EOEEs) are heterogeneous epileptic disorders caused by various abnormalities in causative genes including point mutations and copy number variations (CNVs). In this study, we performed targeted capture and sequencing of a subset of genes to detect point mutations and CNVs simultaneously. Methods We designed complementary RNA oligonucleotide probes against the coding exons of 35 known and potential candidate genes. We tested 68 unrelated patients, including 15 patients with previously detected mutations as positive controls. In addition to mutation detection by the Genome Analysis Toolkit, CNVs were detected by the relative depth of coverage ratio. All detected events were confirmed by Sanger sequencing or genomic microarray analysis. Key Findings We detected all positive control mutations. In addition, in 53 patients with EOEEs, we detected 12 pathogenic mutations, including 9 point mutations (2 nonsense, 3 splice‐site, and 4 missense mutations), 2 frameshift mutations, and one 3.7‐Mb microdeletion. Ten of the 12 mutations occurred de novo; the other two had been previously reported as pathogenic. The entire process of targeted capture, sequencing, and analysis required 1 week for the testing of up to 24 patients. Significance Targeted capture and sequencing enables the identification of mutations of all classes causing EOEEs, highlighting its usefulness for rapid and comprehensive genetic testing.